2022
DOI: 10.12779/dnd.2022.21.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Associated With Successful Nonpharmacological Interventions for People With Dementia

Abstract: Background and purpose We investigated existing nonpharmacological programs for people with dementia (PWD) to explore critical factors related to the effectiveness of these types of programs. Methods We conducted a qualitative systematic literature review to identify nonpharmacological intervention programs developed for PWD and reviewed 36 randomized controlled trials. Among several outcomes reported in each study, we focused on the most common outcomes including quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…In der DeTaMAKS-Studie, in der Menschen mit leichter oder mittlerer Demenz in der Tagespflege untersucht wurden, zeigte sich in der offenen Studienphase, in der die Intervention nicht mehr unter kontrollierten Bedingungen durchgeführt wurde (alle Einrichtungen waren geschult, die Anwendung der Intervention war freigestellt), eine geringere Effektstärke als während der kontrollierten Phase [13,14]. Auch andere Studien zeigten, dass die Wirksamkeit einer Intervention substanziell von der "ordnungsgemäßen" Durchführung der Maßnahme beeinflusst wird [15]. Manualtreue, das heißt, dass eine Intervention exakt nach Vorgabe des Manuals durchgeführt wird, scheint somit einen nicht unerheblichen Einfluss auf die Wirkung einer Intervention zu haben.…”
Section: Manualtreueunclassified
See 1 more Smart Citation
“…In der DeTaMAKS-Studie, in der Menschen mit leichter oder mittlerer Demenz in der Tagespflege untersucht wurden, zeigte sich in der offenen Studienphase, in der die Intervention nicht mehr unter kontrollierten Bedingungen durchgeführt wurde (alle Einrichtungen waren geschult, die Anwendung der Intervention war freigestellt), eine geringere Effektstärke als während der kontrollierten Phase [13,14]. Auch andere Studien zeigten, dass die Wirksamkeit einer Intervention substanziell von der "ordnungsgemäßen" Durchführung der Maßnahme beeinflusst wird [15]. Manualtreue, das heißt, dass eine Intervention exakt nach Vorgabe des Manuals durchgeführt wird, scheint somit einen nicht unerheblichen Einfluss auf die Wirkung einer Intervention zu haben.…”
Section: Manualtreueunclassified
“…The open study phase means that the intervention was no longer carried out under controlled conditions (all facilities were trained, the application of the intervention was optional). Other studies have also shown that the effectiveness of an intervention is substantially influenced by the "proper" implementation of the intervention [15]. Therapy fidelity (i. e. when an intervention is carried out in exact accordance with the manual) thus seems to have a significant influence on the effect of an intervention.…”
Section: Therapy Fidelitymentioning
confidence: 99%